Bioactive phytoconstituents of ethanolic extract from Chromolaena odorata leaves interact with vascular endothelial growth factor and cyclooxygenase-2: A molecular docking study - T R Teuku Husni; Darmawi Darmawi; Azwar Azwar; Kurnia Fitri Jamil (Wolters Kluwer Medknow Publications, 2023)
Chromolaena odorata is an invasive plant with a broad spectrum of medicinal properties, including wound healing. This study aimed to evaluate the interaction of the already identified bioactive phytoconstituents from ethanolic extracts of C. odorata leaves with two angiogenesis-related proteins - vascular endothelial growth factor (VEGF) and cyclooxygenase-2 (COX-2) in silico. A molecular docking protocol was performed on AutoDock Vina employing the molecular structure of VEGF (3HNG) and COX-2 (3LN1) downloaded from the Protein Data Bank. The results reveal that most of the phytoconstituents possess strong binding affinity, where β-tocopherol and squalene have the highest values. In conclusion, it is highly possible that the phytoconstituents of C. odorata from the ethanolic leaf extract perform an interaction with VEGF and COX-2 and affect their activities.